Length-weight relationship and relative condition factor of Indian river shad Gudusia chapra (Hamilton, 1822) in oxbow lakes of Bangladesh - Moumita Choudhury; Md. Aktarul Islam; Md. Anisur Rahman; Md. Monjurul Islam; Anusree Biswas; Nadia S. Kashmi (Journal of Fisheries, 2026)
Length–weight relationships (LWRs) and the relative condition factor are crucial parameters in fisheries stock assessment studies. In this study, LWRs and the condition factor of the Indian river shad Gudusia chapra (Hamilton, 1822) were examined from three oxbow lakes (locally known as baor; 42–166 mm, 0.76–24.93 g) in Bangladesh. A total of 924 specimens were collected from Baluhar (n = 316), Purapara (n = 287) and Khushna (n = 321) oxbow lakes across three seasons (pre-monsoon, monsoon and post-monsoon) during March–December 2022 using standardized fishing nets. In Baluhar Baor, the lowest (2.588) and highest (3.017) b values were recorded in the post-monsoon and monsoon seasons, respectively. In Purapara and Khushna oxbow lakes, these values ranged from 2.893 (post-monsoon) to 2.972 (monsoon) and from 2.748 (post-monsoon) to 2.883 (monsoon), respectively. The coefficient of correlation (r) exhibited a consistent trend across all length categories as well as between seasons (all r² > 0.96). The present study will contribute to the development of future strategies for the sustainable management of G. chapra in the oxbow lakes of Bangladesh and similar aquatic ecosystems.